Examining functional Near-Infrared Spectroscopy as a tool to study brain function in bilinguals - Pliatsikas, Christos (Frontiers in Language Sciences, 2024)
There is increasing evidence that using more than one languages has significant effects on brain function. These effects have been observed in the developing, adult and ageing brain, and have been suggested to have implications for cognitive and brain decline in bilinguals and multilinguals. Aside from extensive investigations with behavioral methods, such effects are now commonly investigated with functional neuroimaging methods, mostly functional Magnetic Resonance Imaging (fMRI) and electroencephalography (EEG). A relatively underused method in the field is functional Near-Infrared Spectroscopy (fNIRS), which carries several advantages over more established methods, including being appropriate for use with infants and children, but also with older and diseased samples. This paper provides an overview of the method and an account of how it has been used in the field of bilingual cognition. It concludes with suggestions of how the method can be best utilized in future research, highlighting it as a method with a strong potential for updating existing theories on the effects of bilingualism on brain function.